Strategies to Improve Bioavailability and In Vivo Efficacy of the Endogenous Opioid Peptides Endomorphin-1 and Endomorphin-2 - De Marco, Rossella; Janecka, Anna (Current Topics in Medicinal Chemistry, 2016)
Morphine and the other alkaloids found in the opium poppy plant still represent the preferred therapeutic tools to treat severe pain in first aid protocols, as well as chronic pain. The use of the opiate alkaloids is accompanied by several unwanted side effects; additionally, some forms of pain are resistant to standard treatments (e.g. neuropathic pain from cancer). For these reasons, there is currently renewed interest in the design and assay of modified versions of the potent endogenous opioid peptides endomorphin-1 and endomorphin-2. This review presents a selection of the strategies directed at preparing highly stable peptidomimetics of the endomorphins, and of the strategies aimed at improving central nervous system bioavailability, for which increased in vivo antinociceptive efficacy was clearly demonstrated.
Keywords: Blood brain barrier